Identifying Mild Cognitive Impairment in Parkinson’s Disease With Electroencephalogram Functional Connectivity - Cai, Min; Dang, Ge; Su, Xiaolin; Zhu, Lin; Shi, Xue; Che, Sixuan; Lan, Xiaoyong; Luo, Xiaoguang; Guo, Yi (Frontiers in Aging Neuroscience, 2021)
Objective: Cognitive impairment occurs frequently in Parkinson’s disease (PD) and negatively impacts the patient’s quality of life. However, its pathophysiological mechanism remains unclear, hindering the development of new therapies. Changes in brain connectivity are related to cognitive impairment in patients with PD, with the dorsolateral prefrontal cortex (DLPFC) being considered the essential region related to PD cognitive impairment. Nevertheless, few studies have focused on the global connectivity responsible for communication with the DLPFC node, the posterior division of the middle frontal gyrus (PMFG) in patients with PD; this was the focus of this study. Methods: We applied resting-state electroencephalography (EEG) and calculated a reliable functional connectivity measurement, the debiased weighted phase lag index (dWPLI), to examine inter-regional functional connectivity in 68 patients with PD who were classified into two groups according to their cognitive condition. Results: We observed altered PMFG-based functional connectivity associated with cognitive impairment in patients with PD in the theta frequency bands under the eyes closed condition. Further analysis using logistic regression and receiver operating characteristic (ROC) curves found that this abnormal functional connectivity was an independent risk factor for cognitive impairment (odds ratio [OR]: 2.949, 95% confidence interval [CI]: 1.294-6.725, p= 0.01 for left PMFG; OR: 11.278, 95%CI: 2.578-49.335, p= 0.001 for right PMFG, per 0.1 U), and provided moderate classification power to discriminate between cognitive abilities in patients with PD (area under the ROC curve [AUC]= 0.770 for left PMFG; AUC=0.809 for right PMFG). Conclusion: These preliminary findings indicate that abnormal PMFG-based functional connectivity patterns associated with cognitive impairment in the theta frequency bands under the eyes closed condition and altered functional connectivity patterns have the potential to act as reliable biomarkers for identifying cognitive impairment in patients with PD.